Bioinformatic analysis of chromatin organization and biased expression of duplicated genes between two poplars with a common whole-genome duplication. (10th March 2021) - Zhang, Le; Zhao, Jingtian; Bi, Hao; Yang, Xiangyu; Zhang, Zhiyang; Su, Yutao; Li, Zhenghao; Zhang, Lei; Sanderson, Brian J; Liu, Jianquan; Ma, Tao
Abstract: The nonrandom three-dimensional organization of chromatin plays an important role in the regulation of gene expression. However, it remains unclear whether this organization is conserved and whether it is involved in regulating gene expression during speciation after whole-genome duplication (WGD) in plants. In this study, high-resolution interaction maps were generated using high-throughput chromatin conformation capture (Hi-C) techniques for two poplar species, Populus euphratica and Populus alba var. pyramidalis, which diverged 14 Mya after a common WGD. We examined the similarities and differences in the hierarchical chromatin organization between the two species, including A/B compartment regions and topologically associating domains (TADs), as well as in their DNA methylation and gene expression patterns. We found that chromatin status was strongly associated with epigenetic modifications and gene transcriptional activity, yet the conservation of hierarchical chromatin organization across the two species was low. The divergence of gene expression between WGD-derived paralogs was associated with the strength of chromatin interactions, and colocalized paralogs exhibited strong similarities in epigenetic modifications and expression levels. Thus, the spatial localization of duplicated genes is highly correlated with biased expression during the diploidization process. This study provides new insights into the evolution of chromatin organization and transcriptional regulation during the speciation process of poplars after WGD.